2020
DOI: 10.1002/pchj.344
|View full text |Cite
|
Sign up to set email alerts
|

Social anhedonia and social functioning: Loneliness as a mediator

Abstract: Social anhedonia is associated with reduced social functioning and diminished reward from social interactions. Individuals expressing social anhedonia are likely to experience reduced social connectedness and feel lonely. Loneliness is also associated with reduced social functioning. Therefore, loneliness could account for the relationship between social anhedonia and social functioning. We aimed to determine whether loneliness mediates the relationship between social anhedonia and reduced social functioning. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 75 publications
2
24
0
Order By: Relevance
“…The level of loneliness reported by this sample is markedly elevated and requires further comment. Across several comparison samples available in past research, the level of loneliness in the present sample of MAPs is elevated when compared with that of university students ( d = 1.64, Russell, 1996; d = 0.95, Tan et al, 2020), community-dwelling adults ( d = 1.74, Knight et al, 1988), and adults over the age of 65 ( d = 2.35, Ausín et al, 2019), gay, lesbian, and bisexual adults ( d = 0.63, Kakoullis, 2001; d = 0.84, Martin & Knox, 1997), and even individuals with histories of sexual offending ( d = 0.64, Beggs & Grace, 2011; d = 0.86, Elliott et al, 2009; d = 0.53, Marshall et al, 1998; d = 1.01, Olver et al, 2014; d = 0.91, Wielinga et al, 2019); the lattermost being a population characterized as experiencing elevated rates of loneliness (Marshall, 1989). These comparisons, while not representing a systematic review of the available literature, suggest MAPs experience markedly higher rates of loneliness and may further emphasize loneliness as an important risk factor for mental health concerns in this population 6…”
Section: Discussionmentioning
confidence: 60%
“…The level of loneliness reported by this sample is markedly elevated and requires further comment. Across several comparison samples available in past research, the level of loneliness in the present sample of MAPs is elevated when compared with that of university students ( d = 1.64, Russell, 1996; d = 0.95, Tan et al, 2020), community-dwelling adults ( d = 1.74, Knight et al, 1988), and adults over the age of 65 ( d = 2.35, Ausín et al, 2019), gay, lesbian, and bisexual adults ( d = 0.63, Kakoullis, 2001; d = 0.84, Martin & Knox, 1997), and even individuals with histories of sexual offending ( d = 0.64, Beggs & Grace, 2011; d = 0.86, Elliott et al, 2009; d = 0.53, Marshall et al, 1998; d = 1.01, Olver et al, 2014; d = 0.91, Wielinga et al, 2019); the lattermost being a population characterized as experiencing elevated rates of loneliness (Marshall, 1989). These comparisons, while not representing a systematic review of the available literature, suggest MAPs experience markedly higher rates of loneliness and may further emphasize loneliness as an important risk factor for mental health concerns in this population 6…”
Section: Discussionmentioning
confidence: 60%
“…5 Loneliness, one of the subjective measures of psychological wellbeing, has been repeatedly demonstrated to be associated with poor social functioning and increased risks of developing a variety of physical health and mental problems. 10,11 Loneliness has been defined as the absence of socially integrative relationships and of intimate relationships. 12 Previous studies revealed that lower perceived social support was found to be a significant predictor of greater impairment in functioning in BD, 12 but less literature has directly reported an association between loneliness and functional impairments in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Loneliness, one of the subjective measures of psychological wellbeing, has been repeatedly demonstrated to be associated with poor social functioning and increased risks of developing a variety of physical health and mental problems 10,11 . Loneliness has been defined as the absence of socially integrative relationships and of intimate relationships 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Loneliness is therefore a common negative emotional experience during adolescence ( Shevlin et al, 2014 ; Goossens, 2018 ) that is detrimental to both physical and mental health ( Holt-Lunstad et al, 2015 ; Kearns et al, 2015 ). Indeed, many studies have found that loneliness makes significantly impact to individuals and society, such as inducing depression ( Kılınç et al, 2020 ; Wang et al, 2021 ), affecting social function ( Tan et al, 2020 ), and leading to problematic behaviors ( McKay et al, 2017 ). Overall, the above literature clearly shows that loneliness adversely affects physical and mental health.…”
Section: Introductionmentioning
confidence: 99%